1992
DOI: 10.1113/jphysiol.1992.sp019286
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation restores activity of L‐type calcium channels after rundown in inside‐out patches from rabbit cardiac cells.

Abstract: SUMMARY1. Rundown of L-type calcium channels was studied in inside-out patches made from single isolated rabbit ventricular myocytes, using barium as the charge carrier.2. In the cell-attached patches single-channel activity was stable for more than 15 min after the patch pipette sealed. f-Receptor stimulation by isoprenaline caused a characteristic increase in opening probability and the appearance of prolonged openings. When the patch was excised to the inside-out configuration and exposed to a simple ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 39 publications
7
71
0
Order By: Relevance
“…26 In addition, it has been suggested that Ca 2ϩ channels in cardiac myocytes are phosphorylated in the absence of any neurohormonal stimulation of the cell and that this basal phosphorylation is necessary to maintain normal channel function. 25,27 This is illustrated by the observation that the rundown of Ca 2ϩ channels following membrane patch excision is reversed by application of MgATP and PKA at the inside face of the membrane. 27 The present finding that interventions known to stimulate cAMP-dependent phosphorylation directly (␤-adrenergic cell exposure, intracellular cAMP application) or indirectly (phosphatase inhibition) restore I Ca in HF myocytes indicates that reduced basal cAMP-dependent regulation of I Ca could be an important mechanism underlying its decrease during HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In addition, it has been suggested that Ca 2ϩ channels in cardiac myocytes are phosphorylated in the absence of any neurohormonal stimulation of the cell and that this basal phosphorylation is necessary to maintain normal channel function. 25,27 This is illustrated by the observation that the rundown of Ca 2ϩ channels following membrane patch excision is reversed by application of MgATP and PKA at the inside face of the membrane. 27 The present finding that interventions known to stimulate cAMP-dependent phosphorylation directly (␤-adrenergic cell exposure, intracellular cAMP application) or indirectly (phosphatase inhibition) restore I Ca in HF myocytes indicates that reduced basal cAMP-dependent regulation of I Ca could be an important mechanism underlying its decrease during HF.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 This is illustrated by the observation that the rundown of Ca 2ϩ channels following membrane patch excision is reversed by application of MgATP and PKA at the inside face of the membrane. 27 The present finding that interventions known to stimulate cAMP-dependent phosphorylation directly (␤-adrenergic cell exposure, intracellular cAMP application) or indirectly (phosphatase inhibition) restore I Ca in HF myocytes indicates that reduced basal cAMP-dependent regulation of I Ca could be an important mechanism underlying its decrease during HF. The high value of the EC 50 of the ISO effect on I Ca compared with published data might reflect tissue specificity of, for instance, the density of the ␤-adrenergic receptors as reported in neonatal dog heart.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is referred to as rundown and can be considered as a failure of the mechanism by which the basal activity of the channel is maintained (1,2). So far, several mechanisms have been proposed for the run-down of Ca 2+ channels, including dephosphorylation of protein kinase A (PKA)-mediated phosphorylation (3) and proteolysis induced by calpain, a Ca…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is referred to as run-down (2) and can be considered as a failure of the mechanism by which basal activity of the channel is maintained (3). So far, several mechanisms have been suggested for run-down, including proteolysis of the channel and dephosphorylation of the phosphorylation mediated by cAMP-dependent protein kinase (PKA) (2,4). Recent work also shows that phosphatidylinositol-4,5-bisphosphate (PIP 2 ) can stabilize the activity of P / Q-type Ca 2+ channels (5,6).…”
Section: Introductionmentioning
confidence: 99%